Analysis of Learning Commitment and Interest in Learning with Learning Outcomes of Building Engineering Education Students in University - Kembuan, Djubir R. E.; Daud, Metsi (International Journal of Information Technology and Education, 2024)
This research aims to analyze: (1) the relationship between learning commitment and learning outcomes of Building Engineering Education students, Faculty of Engineering, Manado State University (PTB FT Unima), (2) the relationship between learning interest and learning outcomes of PTB FT Unima students, and (3) the relationship between commitment to learning, and interest in learning simultaneously with the learning outcomes of PTB FT Unima students. This research design is quantitative research with a survey approach. From the research results: 1) there is a relationship between learning commitment and learning outcomes of PTB FT Unima students, and contributes 23.62%; 2) there is a relationship between interest in learning and learning outcomes of PTB FT Unima students, and provides a contribution of 10.24%; 3) there is a relationship between commitment to learning and interest in learning simultaneously with the learning outcomes of PTB FT Unima students, and provides a contribution of 23.72%. Thus, increasing commitment to learning and interest in learning is one of the factors supporting the learning outcomes of PTB FT Unima students. The results imply that the higher the commitment to learning and interest in learning, the higher the learning outcomes of PTB FT Unima students. This fact proves that commitment to learning and interest in learning simultaneously provide a significant relationship with the learning outcomes of PTB FT Unima students.